1988
DOI: 10.1210/mend-2-11-1009
|View full text |Cite
|
Sign up to set email alerts
|

Unlinked Regulation of the Sensitivity of Primary Glucocorticoid-Inducible Responses in Mouse Mammary Tumor Virus Infected Fu5-5 Rat Hepatoma Cells

Abstract: The enzyme tyrosine aminotransferase (TAT) is induced by unusually low concentrations of glucocorticoids in Fu5-5 cells. We have isolated clones of Fu5-5 cells infected with mouse mammary tumor virus (MMTV) in order to simultaneously compare the glucocorticoid regulation of the host cell gene, TAT, with that of another primary inducible gene, MMTV. In the two clones that were examined in detail, MMTV RNA induction occurred at 4- to 11-fold higher concentrations of dexamethasone than those needed for induction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…1 produced substantially more agonist activity, but were still unable to produce any of the 27-kDa fragment that would be expected on the basis of the steroid's partial antagonist activity. This lack of correlation might have been anticipated since the amount of agonist activity displayed by a given receptor-antiglucocorticoid complex is usually not constant, but varies with parameters such as the gene examined (17,46,65), the presence of cis-acting elements (66 -69), and the total amount of GR present in the cell (51).…”
Section: Discussionmentioning
confidence: 99%
“…1 produced substantially more agonist activity, but were still unable to produce any of the 27-kDa fragment that would be expected on the basis of the steroid's partial antagonist activity. This lack of correlation might have been anticipated since the amount of agonist activity displayed by a given receptor-antiglucocorticoid complex is usually not constant, but varies with parameters such as the gene examined (17,46,65), the presence of cis-acting elements (66 -69), and the total amount of GR present in the cell (51).…”
Section: Discussionmentioning
confidence: 99%
“…The EC 50 was initially thought to be determined by the affinity of steroid binding to cognate receptor (18 -20). However, reports of different dose-response curves for various genes within a cell for the same receptor-steroid complex indicate the involvement of additional parameters (21)(22)(23)(24)(25)(26)(27). Furthermore, the EC 50 can even change for the same gene under different cellular conditions (28,29).…”
mentioning
confidence: 99%
“…Whereas those mechanisms regulating the level of response to saturating concentrations of agonist steroids should persist at subsaturating concentrations, thereby leaving the EC 50 of the dose-response curve unaffected, the converse is not necessarily true. In fact, we have reported that the doseresponse curve for TAT gene induction in Fu5-5 cells is leftshifted (to give a lower EC 50 ) relative to the same gene in HTC cells (18 -21) or to a different gene in the same Fu5-5 cells (19,(21)(22)(23)(24). Thus, physiological concentrations of glucocorticoid elicited a greater percentage of the maximal induction of the TAT gene in Fu5-5 cells than of any other genes examined.…”
mentioning
confidence: 99%